EMPLOYING DIGITAL TECHNIQUES IN THE PRODUCTION OF CHILD TELEVISION DRAMA (Journal of the College of Basic Education, 2019)
Technical developments play a very important role in human life in general and a distinctive and creative role in the arts, including television drama arts where digital technologies have added high potential and impact on the picture productions, and perhaps the most important television drama dedicated to children and cartoons, with its values ​​and educational and educational content and others, Digital technologies have become a distinct technical tools that contribute to clarify the aesthetic features of the image products, so this research came to shed light on the most important technical and output processors through the use of digital technologies in every detail p Mechanism dedicated the picture production for children